Nano-Technological Approaches for Targeting Kidney Diseases With Focus on Diabetic Nephropathy: Recent Progress, and Future Perspectives - Lin, Bo; Ma, Ying-Yu; Wang, Jun-Wei (Frontiers in Bioengineering and Biotechnology, 2022)
Diabetic nephropathy (DN) is the leading cause of end-stage renal disease worldwide. With the rising prevalence of diabetes, the occurrence of DN is likely to hit pandemic proportions. The current treatment strategies employed for DN focus on the management of blood pressure, glycemia, and cholesterol while neglecting DN's molecular progression mechanism. For many theranostic uses, nano-technological techniques have evolved in biomedical studies. Several nanotechnologically based theranostics have been devised that can be tagged with targeting moieties for both drug administration and/or imaging systems and are being studied to identify various clinical conditions. The molecular mechanisms involved in DN are discussed in this review to assist in understanding its onset and progression pattern. We have also discussed emerging strategies for establishing a nanomedicine-based platform for DN-targeted drug delivery to increase medication efficacy and safety, as well as their reported applications